Relationships between rugby sevens performance indicators and international tournament outcomes - Higham, D. G.; Hopkins, W. G.; Pyne, D. B.; Anson, J. M. (Journal of Quantitative Analysis in Sports, 2014)
Objectives: Identifying performance indicators related to rugby sevens competition outcomes will inform development of team tactics that increase the likelihood of success. This study characterized 16 team performance indicators and quantified the effect of changes and differences in performance indicators within and between teams on team ranking in international tournaments.